"It's the work climate that keeps me here": the interplay between the HRM process and emergent factors in the construction of employee experiences. Issue 2 (13th December 2021) - Laiho, Maarit; Saru, Essi; Seeck, Hannele
Abstract : Purpose: The purpose of this paper is to explore the interplay between human resource management (HRM) and emergent factors in constructing a strong HRM climate. Specifically, the paper aims to shed light on how employee perceptions of the HRM process and emergent factors together construct a strong HRM climate, i.e. employees' shared perceptions of HRM. Design/methodology/approach: The paper uses qualitative interview data (managers and employees) from two organisations operating in Finland. The data are analysed based on a systematic data analysis and gives an illustration of the interplay between high-performance work system and the emergent factors. Findings: The findings illustrate the three types of interplay between HPWS and emergent factors – supplementation, substitution and suffocation – that construct employee experience. Originality/value: The paper extends earlier discussions on the relationship between HRM and employee experience by empirically examining how the HRM process – together with emergent factors – constructs a strong HRM climate. The present study contributes to further theorising and increasing our understanding of the creation of employee experience.